Isolation and Identification of Azadirachtin from fruits of Melia azedarach L. (Meliaceae) - Mehdi, N. S.; Al-Rubeae, H. F.; Ali, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Azadirachtin is a naturally occurring substance that belongs to an organic molecule class which is called tetranortriterpenoids. It is on of the most powerful plant derived insecticides known, its structure is similar to insect hormones called ecdysoncs (Molting Hormone), which control the process of metamorphosis. Azadirachtin has been isolated from fruits of Melia azedarach L. The structure of this compound was determined by spectral studies (IR spectra and GC Mass spectra) and denitrified by then layer chromotochraphy (TLC).